Pengaruh Service Quality Terhadap Customer Satisfaction dan Customer Loyalty Jasa Penggiriman Jalur Darat Pada PT. Bali Semesta Agung Express di Denpasar - Sumiati, Ni Komang; Sanjaya, Putu Krisna Adwitya; Swara, Ni Nyoman Adityarini Abiyoga Vena (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
Loyal customers are very valuable assets for the company. This study aimed at determining the effect of service quality on the satisfaction and loyalty of the customers through shipping services at PT. Bali Semesta Agung Express in Denpasar. The data was collected by using observation methods, literature study, interview methods, and questionnaires. The sample size was determined by using the Slovin formula, and 100 respondents using the purposive sampling technique and hypothesis testing was carried out by path analysis and single-test. The result of the research shows that: (1) service quality has a positive and significant effect on customer satisfaction, (2) customer satisfaction has a positive and significant effect on customer loyalty, (3) service quality has a positive and significant effect on customer loyalty, and (4) service quality has a positive and significant effect towards customer loyalty through the customer satisfaction. Based on the research results, improving the service quality and customer satisfaction will increase customer loyalty at PT. Bali Semesta Agung Express in Denpasar.